Differences in second trimester risk estimates for trisomy 21 between Maglumi X3/Preaccu and Immulite/Prisca systems - Üstündağ Yasemin; Huysal Kağan; Yeşil Meryem Rümeysa (Türk Biyokimya Dergisi)
Maternal serum alpha-fetoprotein (AFP), human chorionic gonadotropin (HCG) or free β-HCG, and unconjugated estriol (uE3) concentrations are used to screen trisomy 21 in the second trimester. The performance of different analytical platforms has an impact on individual risk estimates. The aim of this study is to compare the multiple of median (MoM) values and risk estimates generated by Maglumi X3 analyzer/Preaccu software with the Immulite 2000 XPi device/Prisca software.